Perlindungan Hukum Terhadap Kaum Mustadh’afin: Studi Komparatif Hukum Islam dan Hukum Positif - Amrin, Shafwan; Marilang (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2022)
This article describes the Mustadh'afin people as people who are weakened from various aspects, both from the lack and lack of attention from the government or the largest Muslim community in Indonesia. Islamic law as the law of causal belief at the end of life makes the Mustadh'Afin people still lack of concern for helping and helping each other and Positive Law as a basic reference for laws or regulations that have been firm to protect, guide and maintain marginalized people. The mustadh'afin as the axis of social dynamics in the scope of the state, where there is a lack of role and empowerment from the parties responsible for addressing and supporting their gap issues. Islam and Positive Law. Because conditionally now it has been shown how the life and fate of the Mustadh'afin themselves are. The results of this study The Mustadh'Afin as a people who are weakened, in Islamic Law has become an order to protect it as in several holy verses of the Qur'an and Hadith, and Positive Law has been firm in several laws to protect and maintain the Mustadhg' Affin. The mandate of the 1945 Constitution emphasizes the obligation of the state to provide the greatest prosperity for the people, and it is the responsibility of the government to meet the needs of its citizens.